Še nekaj misli ob prispevku Slovenec sem in kdo je več? - Kristan, Silvo (Šport (Ljubljana), 2023)
A more detailed hermeneutical1 dissection of the article with the above title revealed a number of other “curiosities” that, for the sake of the credibility of sport theory and the clarification of the slip-ups of renowned experts, are worthy of being recorded in a peer-reviewed journal. If these comments had been published in another journal, they would certainly have bypassed most sports experts, and that would certainly not have been a good thing. Therefore, after a second reading of the above-mentioned article, I am supplementing my controversial contribution entitled In the name of accuracy and truth, which the editors of the Sport journal kindly published in issue 3–4, 2022. I will only keep to myself my opinion on the unnecessary political barbs with which the author of the above-mentioned article casually peppers the text without actually clarifying anything (apart from the author's identity). I will also keep to myself the idea of the chaotic nature of the presentation and treatment of the “subject and problem” (as we say in science), because it is subjective and based on the stricter criteria of monograph writing.
Keywords: hermenevtika; šport; športna kultura; telesna dejavnost; telesna kultura